TFE3 fusion proteins drive TFE3 rearranged renal cell carcinoma progression via PGC-1α-mediated fatty acid oxidation - Feng, Fan; Xu, Yanhao; Deng, Zhenggen; Dong, Xiang; Chen, Guijuan; Ma, Wenliang; Li, Dongmei; Gan, Weidong (Frontiers in Immunology, 2026)
IntroductionTFE3 rearranged renal cell carcinoma (TFE3 rRCC) is a distinct and aggressive subtype of RCC characterized by poor prognosis. While TFE3 fusion proteins are central to its pathogenesis, their specific roles in tumor progression, particularly regarding metabolic regulation, remain incompletely understood. This study investigates whether TFE3 fusion proteins promote TFE3 rRCC progression by regulating fatty acid oxidation (FAO).MethodsTo elucidate the regulatory mechanisms, transcriptome sequencing, Western blotting, real-time quantitative PCR, dual-luciferase reporter assays, Chromatin Immunoprecipitation assays, and Seahorse XF96 analysis were employed to examine how TFE3 fusion proteins regulate the PGC-1α/PPARα/CPT1A axis and its impact on mitochondrial FAO in tumor cells. Additionally, bioinformatics analysis of publicly available TCGA data was conducted to assess the expression of PGC1A and CPT1A in various kidney cancer subtypes and their correlation with patient prognosis.ResultsTFE3 fusion proteins were found to transcriptionally upregulate PGC-1α, thereby increasing the tumor cells dependency on mitochondrial FAO. Mechanistically, PGC-1α co-activated PPARα to promote the expression of CPT1A, a rate-limiting enzyme in FAO. This TFE3/PGC-1α/CPT1A axis enhanced tumor cell proliferation, migration, and invasion. TCGA data analysis revealed that low expression levels of PGC1A and CPT1A in general kidney cancer are associated with poor patient prognosis. Conversely, in our specific TFE3 rRCC cohort, high expression of PGC-1α and CPT1A correlated with poorer survival outcomes, highlighting their clinical significance.ConclusionsTFE3 fusion proteins enhance FAO and drive TFE3 rRCC progression via the PGC-1α/PPARα/CPT1A axis. Targeting CPT1A could inhibit tumor cell proliferation, suggesting that this pathway may serve as a potential therapeutic target for TFE3 rRCC.